A New (3+1) Date-Jimbo-Kashiwara-Miwa Equation: Solutions and Conservation Laws - Goitsemang, T.; Muatjetjeja, B.; Mothibi, D. M.; Motsumi, T. G. (Journal of Applied Nonlinear Dynamics, 2026)
This study aims to establish exact solutions of a new (3+1) Date-Jimbo-Kashiwara-Miwa equation. The method of the modern group analysis will be implemented to derive exact solutions of the aforementioned equation. In addition, the variational method will be employed to construct conserved vectors of a new (3+1) Date-Jimbo-Kashiwara-Miwa equation. Furthermore, a brief physical interpretation of these conserved vectors will be mentioned.